(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Modern drawing of the future plays an important role in the development of professional skills of teachers, increase of efficiency of educational system, training of students with modern knowledge and skills. This article presents information on the formation of professional competences of teachers.